PO-32 - Patient, tumour and operative factors influencing perioperative hypercoagulability in colorectal cancer. Issue 140 (April 2016) - Clouston, H.W.; Rees, P.A.; Shaker, H.; Duff, S.; Kirwan, C.C.
Abstract : Introduction: Up to 6% of patients develop venous thromboembolism (VTE) following elective colorectal cancer surgery despite thromboprophylaxis. Clinical practices for perioperative thromboprophylaxis remains variable, particularly the use and duration of extended thromboprophylaxis. Identification of factors associated with a prolonged postoperative hypercoagulable state may allow the development of algorithms that allow more targeted thromboprophylaxis. Aim: To identify patient, tumour and surgical risk factors for prolonged (two and six weeks) hypercoagulability in colorectal cancer patients undergoing surgical resection. Materials and Methods: In a prospective cohort study (Cancer-induced Hypercoagulability As a Marker of Prognosis [CHAMPion]), plasma d-dimer was measured at 2 and 6 weeks post-operatively in patients undergoing elective, curative resection for colorectal cancer. Hypercoagulability (raised D-dimer) at 2 and 6 weeks was correlated with patient, tumour and operative factors. Results: Of the 62 patients recruited (median age 69 years [range 39-90]), 37 were male. D-dimer was increased in females compared to males at six weeks (geometric mean (GM) 1, 287 ng/ml [95% CI 944 – 1, 755 vs. 821 ng/ml (95% CI 633 – 1064) p = 0.03]. Age, smoking, hypertension, use of antiplatelet medication, BMI and WHO performance status were not associated with a prolonged hypercoagulable state. There were no tumour factors (including size/T stage/lymph node involvement/differentiation) associated with a prolonged hypercoagulable state. D-dimer was increased in patients undergoing open surgery (n = 39) compared to laparoscopic surgery (n = 23) at 2 weeks (GM 2, 337 ng/ml [95% CI 1, 806-3, 023] vs. 1, 212 ng/ml [95% CI 898-1, 629], p = 0.001) and 6 weeks (GM 1, 162 ng/ml [95% CI 818-1647] vs. 723 ng/ml [95% CI 533-982]p = 0.04). Operative time was not associated with prolonged hypercoagulability. D-dimer had a trend to be increased at 2 weeks in patients receiving perioperative blood transfusions (n = 8) compared to those that did not (n = 54) (GM 2, 618 ng/ml [95% CI 1, 525-4, 536] vs. 1613 ng/ml [95% CI 1, 236 – 2, 100] p = 0.08). Conclusions: Even in this relatively small cohort of patients female gender, open surgery and receiving a blood transfusion are associated with on-going hypercoagulability up to six weeks post operation. This may represent a group where thromboprophylaxis should be targeted.